2021
DOI: 10.1111/2041-210x.13658
|View full text |Cite
|
Sign up to set email alerts
|

A field‐friendly method of measuring faecal glucocorticoid metabolite concentration as a simple stress checker in snow leopards

Abstract: 1. The hormonal analysis of excrement has been employed to non-invasively assess the physiological conditions of domestic, experimental, zoo and wild animals to.However, conventional hormone analysis techniques require frozen and refrigerated reagents, and laboratory equipment; therefore, it is almost impossible to obtain the results on-site. This study attempted to establish a method for the simple and rapid quantitative on-site analysis of faecal glucocorticoid metabolite (fGM) concentrations; this method in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Stetz et al. [7] found that in free-ranging grizzly bears and black bears ( Ursus americanus ), fecal glucocorticoid metabolites decreased with exposure to precipitation and increased with exposure outdoors, even though Kinoshita [8] found that ultraviolet exposure did not influence hormone metabolite concentrations in snow leopard feces. For African elephants, fecal glucocorticoid metabolites decreased, and fecal progestogen and estrogen metabolites increased as time since defecation increased [9] .…”
Section: Methods Validationmentioning
confidence: 99%
“…Stetz et al. [7] found that in free-ranging grizzly bears and black bears ( Ursus americanus ), fecal glucocorticoid metabolites decreased with exposure to precipitation and increased with exposure outdoors, even though Kinoshita [8] found that ultraviolet exposure did not influence hormone metabolite concentrations in snow leopard feces. For African elephants, fecal glucocorticoid metabolites decreased, and fecal progestogen and estrogen metabolites increased as time since defecation increased [9] .…”
Section: Methods Validationmentioning
confidence: 99%